Disentangling genes, attachment, and environment: A systematic review of the developmental psychopathology literature on gene–environment interactions and attachment. (February 2020) - Golds, Lisa; de Kruiff, Karina; MacBeth, Angus
Abstract: The role of genetics in relation to attachment is of continued interest to developmental psychology. Recent research has attempted to disentangle genetic main effects, environmental effects, and gene and environment (G × E) interactions in the development of attachment security/insecurity and disorganization. We systematically reviewed associations between gene markers and attachment, including G × E interactions, identifying 27 eligible studies. Inconsistent results emerged for associations between both gene effects and G × E interactions on attachment organization. Where G × E interactions used attachment as the environmental factor in the interaction, we observed more consistent results for differential susceptibility of G × E interactions on offspring behavior. Small sample size and heterogeneity in measurement of environmental factors impacted on comparability of studies. From these results, we propose that the future of research into the role of genetic effects in attachment lies in further exploration of G × E interactions, particularly where attachment acts as an environmental factor impacting on other child developmental outcomes emerging from the caregiving environment, consistent with differential susceptibility approaches to developmental psychopathology. In addition, from a methodological perspective, establishing the role of gene markers in such models will require a shift toward contemporary genomics, including genome-wide analysis (including novel genes and chromosomal loci), and epigenetic individual variations.